Analisis Perbandingan Nafkah Pernikahan dalam Kitab Fathul Mu’in dan Fathul Qarib - M. Fatur Anggara; Musthato Musthato; Anggra Prima (CV. ITTC INDONESIA, 2025)
The purpose of this study is to determine the concept of marital maintenance in the Fathul Mu'in and Fathul Qarib books and the comparison between the two books. This type of research is included in the type of library research, namely research whose data collection is carried out by collecting data from various literatures. Where the primary data used in this study are the Fathul Mu'in and Fathul Qarib books. While the secondary data sources in this study were obtained from the Qur'an, Hadith, reference books, articles, journals, theses and theses and other written data that are relevant to the title of this thesis. The results of the analysis of this study show that: The similarities between the two books emphasize the husband's obligation to provide maintenance to his wife and the wife's right to receive maintenance as part of the responsibility of marriage. The difference in the two books is that Fathul Mu'in provides a very detailed explanation of the husband's obligation to provide maintenance to his wife, including food, clothing, shelter, servants, and other needs. This obligation is explained in detail according to the husband's economic condition (rich, sufficient, or poor). Meanwhile, Fathul Qarib provides a more concise explanation but still covers important aspects in providing a living, such as food, side dishes, clothing, household equipment, and housing. This book provides flexibility in implementing the obligation of living, depending on the economic conditions and local customs.